Serum and Urinary Selenium Status in Patients with the Pre-diabetes and Diabetes in Northeast China - Zhou, Qi; Guo, Wenjia; Jia, Yanan; Xu, Jiancheng (Biological trace element research, 2019)
Homeostasis imbalance of selenium (Se) in diabetes has received great attention. This study investigated serum and urinary Se levels in patients with impaired fasting glucose (IFG), impaired glucose tolerance (IGT), type 1 diabetes (T1D), and type 2 diabetes (T2D) in Northeast Chinese populations. From January 2010 to October 2011, patients with IFG ( n = 12), IGT ( n = 15), T1D ( n = 25), T2D ( n = 137), and healthy controls ( n = 50) were enrolled in the First Hospital of Jilin University. Se was detected using inductively coupled plasma spectrometer. The serum Se level was dramatically lower in patients with T1D and was significantly higher in IFG subjects, and the urinary Se concentration was markedly lower in IGT and T2D groups. The serum Se levels were positively correlated with serum zinc (Zn) in both IFG and IGT groups, while urinary Se were positively associated with urinary Zn and copper (Cu) in IGT group. The serum Se levels were positively correlated with serum Cu in both T1D and T2D groups, and urinary levels of Se were positively associated with serum zinc and urinary Cu, Zn, calcium (Ca), and magnesium (Mg) and negatively correlated with serum Ca and Mg in T2D group, while the urinary levels of Se were positively correlated with urinary Zn and Mg both in peripheral neuropathy (DPN) and retinopathy (DR) groups. One month of simvastatin therapy reduced serum Se levels. These results suggest the potential role of Se in diabetes should receive attention.